Deindustrialization : Causes and Implications - Ramaswamy, Ramana (IMF Working Papers; Working Paper ;, 1997)
All advanced economies have experienced a secular decline in the share of manufacturing employment-a phenomenon referred to as deindustrialization. This paper argues that, contrary to popular perceptions, deindustrialization is not a negative phenomenon, but is the natural consequence of the industrial dynamism in an already developed economy, and that North-South trade has had very little to do with deindustrialization. The paper also discusses the implications of deindustrialization for the growth prospects and the nature of labor market arrangements in the advanced economies.